2020
DOI: 10.1371/journal.pone.0238089
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immunodominant linear epitopes from SARS-CoV-2 patient plasma

Abstract: A novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) is the source of a current pandemic (COVID-19) with devastating consequences in public health and economic stability. Using a peptide array to map the antibody response of plasma from healing patients (12) and heathy patients (6), we identified three immunodominant linear epitopes, two of which correspond to key proteolytic sites on the spike protein (S1/S2 and S2') known to be critical for cellular entry. We show biochemical evidence that plas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
100
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 73 publications
9
100
0
Order By: Relevance
“…Two studies demonstrated a lack of association with affinity [115,145], although a moderate correlation with binding affinity was reported in one study [146]. Potently neutralising N specific antibodies were isolated in other studies [115,148], and the potential for antibodies binding to protease cleavage sites as alternatives to RBD isolated from convalescent plasma has also been identified [153], suggesting an important role in preventing antibody dependent enhancement of viral entry.…”
Section: Protective Immunitymentioning
confidence: 98%
“…Two studies demonstrated a lack of association with affinity [115,145], although a moderate correlation with binding affinity was reported in one study [146]. Potently neutralising N specific antibodies were isolated in other studies [115,148], and the potential for antibodies binding to protease cleavage sites as alternatives to RBD isolated from convalescent plasma has also been identified [153], suggesting an important role in preventing antibody dependent enhancement of viral entry.…”
Section: Protective Immunitymentioning
confidence: 98%
“…The targeting of spike proteins by broad-neutralizing antibodies against SARS-CoV-2 offers a potential means of treating and preventing further infections of COVID-19 (Jiang et al, 2020). Evidence on immunodominant epitopes with significantly higher response rates have also been reported (Farrera-Soler et al,2020). Antibody response to SARS-CoV-2 is one of the key immune responses to SARS-CoV-2 which is actively being pursued to develop therapeutic strategies as well as vaccines (Biswas et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
“…This might be the case for SARS-CoV-2 when using proteins sharing high homology with genetically similar, co-circulating, human coronaviruses (hCoV) that are responsible for common cold [ 6 , 7 ]. Studies towards fine dissection of the specific regions on the viral proteins recognized by virus-specific antibodies have been recently published focusing on the S protein [ 6 , 8 , 9 , 10 , 11 ]. Moreover, detailed overviews of the epitope landscape within SARS-CoV-2 confirmed interest on the N protein epitopes as valuable markers [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%